2017
DOI: 10.1186/s12904-017-0209-9
|View full text |Cite
|
Sign up to set email alerts
|

Integration and activity of hospital-based palliative care consultation teams: the INSIGHT multicentric cohort study

Abstract: BackgroundHospital-based Palliative Care Consultation Teams (PCCTs) have a consulting role to specialist services at their request. Referral of patients is often late. Early palliative care in oncology has shown its effectiveness in improving quality of life, thereby questioning the “on request” model of PCCTs. Whether this evidence changed practice is unknown. This multicentre prospective cohort study aims to describe the activity and integration of PCCTs at the patient level.MethodsFor consecutive patients n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 26 publications
7
21
1
2
Order By: Relevance
“…However, our results on the location of death (44.7% of patients died in hospital, emergency room or intensive care units, or rehabilitation unit) are to be interpreted in the French healthcare system in which home care is underdeveloped, as shown by the national mortality data (18.9% of cancer death occurring at home) [31]. This proportion is even lower in our population, as it has been described in similar population from university hospitals [6].…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…However, our results on the location of death (44.7% of patients died in hospital, emergency room or intensive care units, or rehabilitation unit) are to be interpreted in the French healthcare system in which home care is underdeveloped, as shown by the national mortality data (18.9% of cancer death occurring at home) [31]. This proportion is even lower in our population, as it has been described in similar population from university hospitals [6].…”
Section: Discussionsupporting
confidence: 44%
“…The access to palliative care in oncology, for patients with advanced cancers, hinges on hospital-based palliative care consultation teams (PCT). Despite being recommended early in the course of advanced cancer [1][2][3] palliative care is often proposed late and after the stop of antitumoral treatments [4][5][6] with low impact on patient's quality of life [7]. The reasons for this delay are now well known [4,[8][9][10]., Patients and family-related barriers for early referral often include negative image of palliative care and unwillingness to end anti-cancer treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The role of palliative care consultation teams is to provide on-demand services within the hospital [12]. In this qualitative study, the characteristics of the PCCS programme were examined in a structured manner.…”
Section: Discussionmentioning
confidence: 99%
“…transferring patients form inpatient care to homecare). A recent multicentre cohort study in France showed that there is still late referral to palliative care and that the "on request" model which originally characterized these services is gradually being exchanged for the integrated palliative care model [12]. Several studies suggest that even after one visit with the palliative care team in inpatient setting, there are improvements in physical and psychological symptoms, quality of life, as well as patient satisfaction with care [13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The access to palliative care in oncology, for patients with advanced cancers, hinges on hospitalbased palliative care consultation teams (PCT). Despite being recommended early in the course of advanced cancer (1), (2), (3) palliative care is often proposed late and after the stop of antitumoral treatments (4), (5), (6) with low impact on patient's quality of life (7) . The reasons for this delay are now well known (4), (8), (9), (10) .…”
Section: Introductionmentioning
confidence: 99%